Uterine receptor activation in response to uterotonic agents in late-pregnancy rat myometrium following pretreatment with oxytocin: an in vitro study - Li-Mei Liao; Jian-Ying Hu; Ting-Ting Wang; Shao-Qiang Huang (IMR Press, 2021)
Background: Long term exposure to oxytocin reduces the ability of myometrium to respond to oxytocin, leading to oxytocin receptor (OXTR) desensitization. In this study we analyzed the response to other uterotonics such as prostaglandin, as well as investigating prostaglandin E2 receptors (EP3) and prostaglandin F2α receptors (FP). We hypothesized that compensatory mechanisms would increase the expression and activation of FP and EP3 following OXTR desensitization. Methods: Myometrium from late-pregnancy rats was collected in order to assess mRNA expression levels for OXTR, FP, and EP3 using RT-PCR. This was done after 2 hours of pretreatment with 10-6 M oxytocin to induce OXTR desensitization, or equilibration in physiological salt solution (PSS). Myometrium was exposed to increasing concentrations of uterotonic agents (10-10 to 10-5 M) following 2 hours of pretreatment with 10-6 M oxytocin (experimental group) or with PSS (control group). Myometrium from the experimental group was washed with PSS and OXTR expression was assessed using Western blot and RT-PCR. Results: mRNA expression levels for EP3, FP and OXTR were not statistically different between the experimental (OXTR desensitization) and control groups. Compared to the control group, the (mean ± SD) contractile potency of carboprost (pEC50: 7.74 ± 0.56 vs 6.81 ± 0.25, P = 0.03) and maximal contractility of misoprostol (Emax(ratio): 4.44 ± 3.60 vs 1.32 ± 0.22, P = 0.02) were significantly increased in the OXTR desensitization group, while the contractility of oxytocin was significantly reduced (Emax(ratio): 1.62 ± 0.27 vs 2.82 ± 0.98, P = 0.015). No significant differences in myometrial OXTR expression were observed between the PSS, carboprost and misoprostol groups following OXTR desensitization. Discussion: Following OXTR desensitization of myometrium, FP and EP3 activation increased in a compensatory manner, but not FP and EP3 receptor expression.